2003
DOI: 10.1073/pnas.0538059100
|View full text |Cite
|
Sign up to set email alerts
|

Significance and therapeutic potential of the natriuretic peptides/cGMP/cGMP-dependent protein kinase pathway in vascular regeneration

Abstract: Natriuretic peptides (NPs), which consist of atrial, brain, and C-type natriuretic peptides (ANP, BNP, and CNP, respectively), are characterized as cardiac or vascular hormones that elicit their biological effects by activation of the cGMP͞cGMP-dependent protein kinase (cGK) pathway. We recently reported that adenoviral gene transfer of CNP into rabbit blood vessels not only suppressed neointimal formation but also accelerated reendothelialization, a required step for endothelium-dependent vasorelaxation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 35 publications
6
132
0
3
Order By: Relevance
“…a variety of vasculoproliferative processes under pathological conditions. This view is supported by the recent finding that ischemia-induced angiogenesis is impaired in cGKI-deficient mice (28). Others reported that cGMP and cGKI inhibit SMC proliferation in vitro (for reviews, see refs.…”
Section: Activation Of Cgki In Primary Aortic Smcs Stimulates Phenotymentioning
confidence: 76%
“…a variety of vasculoproliferative processes under pathological conditions. This view is supported by the recent finding that ischemia-induced angiogenesis is impaired in cGKI-deficient mice (28). Others reported that cGMP and cGKI inhibit SMC proliferation in vitro (for reviews, see refs.…”
Section: Activation Of Cgki In Primary Aortic Smcs Stimulates Phenotymentioning
confidence: 76%
“…Thus, we wished to obtain insight into which NPR was involved in mediating CNP-induced inhibition of leukocyte rolling. In this regard, we used the selective NPR-C agonist (17), cANF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (because of the lack of availability of selective NPR-B antagonists). cANF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] mimicked the inhibitory actions of CNP on leukocyte recruitment; although this observation only provides circumstantial evidence that CNP exerts its antileukocyte effects via this NPR, it does demonstrate that NPR-C activation is functionally important in the regulation of leukocyte-endothelial cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…CNP (0.1-1 M) was superfused for 10 min, and leukocyte flux was recorded. To investigate the involvement of the NPR-C in responses to CNP, the ability of the selective NPR-C agonist (17), cANF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (1 M) to inhibit leukocyte rolling was also explored.…”
Section: Assessment Of the Effect Of Cnp On Basal Leukocyte Activatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty different random microscopic fields on five different sections from each animal were photographed and analyzed by MetaMorph software. Capillary density was expressed as number of capillaries per high power field (ϫ400) as described previously (27,28).…”
Section: Generation Of Ec-selective Mir-15a Transgenic (Ec-mir-15a Tg)mentioning
confidence: 99%